MiRNA contributions to pediatric‐onset multiple sclerosis inferred from GWAS. Issue 6 (15th May 2019) - Rhead, Brooke; Shao, Xiaorong; Graves, Jennifer S.; Chitnis, Tanuja; Waldman, Amy T.; Lotze, Timothy; Schreiner, Teri; Belman, Anita; Krupp, Lauren; Greenberg, Benjamin M.; Weinstock–Guttman, Bianca; Aaen, Gregory; et al.
Abstract: Objective: Onset of multiple sclerosis (MS) occurs in childhood for approximately 5% of cases (pediatric MS, or ped‐MS). Epigenetic influences are strongly implicated in MS pathogenesis in adults, including the contribution from microRNAs (miRNAs), small noncoding RNAs that affect gene expression by binding target gene mRNAs. Few studies have specifically examined miRNAs in ped‐MS, but individuals developing MS at an early age may carry a relatively high burden of genetic risk factors, and miRNA dysregulation may therefore play a larger role in the development of ped‐MS than in adult‐onset MS. This study aimed to look for evidence of miRNA involvement in ped‐MS pathogenesis. Methods: GWAS results from 486 ped‐MS cases and 1362 controls from the U.S. Pediatric MS Network and Kaiser Permanente Northern California membership were investigated for miRNA‐specific signals. First, enrichment of miRNA‐target gene network signals was evaluated using MIGWAS software. Second, SNPs in miRNA genes and in target gene binding sites (miR−SNPs) were tested for association with ped‐MS, and pathway analysis was performed on associated target genes. Results: MIGWAS analysis showed that miRNA‐target gene signals were enriched in GWAS ( P = 0.038) and identified 39 candidate biomarker miRNA‐target gene pairs, including immune and neuronal signaling genes. The miR‐SNP analysis implicated dysregulation of miRNA binding to target genes in five pathways, mainly involved in immune signaling. Interpretation: Evidence from GWAS suggests that miRNAs play a role in ped‐MS pathogenesis by affecting immune signaling and other pathways. Candidate biomarker miRNA‐target gene pairs should be further studied for diagnostic, prognostic, and/or therapeutic utility.